Perbandingan Efektivitas Pemberian Kombinasi Vitamin C dan Zinc dengan Pemberian Secara Tunggal terhadap Jumlah Sel Spermatogenik Testis Mencit Balb/C yang Diberi Paparan Asap Rokok - Nugraha, Alvian Yuta, dr. Retno Sintowati, M.Sc, dr. Wulandari Berliani Putri (2014)
Background: Smoking is a major health problem in Indonesia and caused more than 200,000 deaths every year. Cigarette smoke contain a very high free radical, one of them is Polynuclear Aromatic Hydrogen (PAH) which can cause testicular atrophy, inhibit spermatogenesis, sperm morphology and damaging. Objective : To determine the effectiveness of the administration of a combination of Vitamin C and Zinc compared with a single administration to the number of spermatogenic cells BALB / c mice which given by cigarette smoke exposure. Methods : This research used experimental methods post test only control group design. The subject used is the strain BALB/c mice which weight 30-40 grams and aged 8-12 weeks. The research sample is divided into 5 groups consisting of positive control group , negative control group, and 3 different of treatment groups. The positive control group and 3 different of treatment groups were given exposure to cigarette smoke for 30 minutes everyday, after that 3 different treatment groups had been given vitamin C for group 1, Zinc for group 2 and the combination for group 3. After 30 days, the spermatogenic cells counts were observed. The analysis of the data using One-Way Anova. Results : The combination of vitamin C (0.2 mg / grbb) and Zinc (0.014 mg / grbb) could increase the spermatogenic cells count of mice compared with mice that were only given cigarette smoke exposure (p = 0.001). Compared with giving of zinc (0,014 mg / grbb) a combination of vitamin C and Zinc increases the spermatogenic cells count was significantly (p = 0.022). However, compared with vitamin C (0.02 mg / grbb) a combination of vitamin C and Zinc were not significantly different (p = 0.096). Conclusion : The combination of vitamin C and Zinc more effective than Zinc only to the increasing of spermatogenic cell counts. Meanwhile, the combination of vitamin C and Zinc compared with vitamin C only has no signifficant difference.